Institute of Ecology and Bioethics of the Cardinal Stefan Wyszyński University - Sandner, Jan (Studia Ecologiae et Bioethicae, 2008)
Preparation of appropriate methodology for teaching about natural resources in accordance with the concept of holistic education is currently becoming one of our major goals. Achievement of these goals is indispensable in the perspective of objectives set within the framework of sustainable development, this article is a general overview of results of studies carried out in 2007 on the condition of holistic environmental education among students of the Institute of Ecology and Bioethics at the Stefan Wyszyński University, the s e studies have strongly emphasized the issue of distinguishing the mereological approach and the holistic approach to the natural environment with the use of modern methods of estimation.